Impact of diethyl ether on emissions of groundnut soapstock biodiesel-diesel blends in a VCR engine - Ragit, S S; Karmakar, Rachan; Mitra, Debasis; Kundu, Krishnendu; Tripathi, Vijay (Edelweiss Applied Science and Technology, 2026)
Growing concerns over diesel engine emissions have increased interest in cleaner and more sustainable fuel blends. This study aimed to evaluate the emission behavior of diethyl ether (DEE) when blended with groundnut soapstock oil methyl ester (GSOME) and diesel fuel in a variable compression ratio (VCR) engine. Experimental investigations were conducted using pure diesel and three GSOME–DEE blended fuels at compression ratios of 14:1, 16:1, and 18:1, while maintaining a constant engine speed of 1500 rpm under varying load conditions. Emissions of nitrogen oxides, carbon monoxide, and unburned hydrocarbons were measured and analyzed. The results indicated that the D80GSOME10-DEE10 blend exhibited the most favorable emission performance among the tested fuels. At full load, this blend achieved significant reductions in NOₓ and CO emissions compared to diesel across all compression ratios, with the highest reductions observed at 18:1. However, an increase in hydrocarbon emissions was also recorded, attributed to rapid fuel vaporization and localized quenching effects. Overall, the study concludes that GSOME–DEE blends, particularly at optimized ratios, can serve as a viable alternative fuel. These findings support the use of DEE-assisted biodiesel blends for emission reduction strategies in VCR diesel engines.